A simple and automated online SPE-LC-MS/MS method for simultaneous determination of olanzapine, fluoxetine and norfluoxetine in human plasma and its application in therapeutic drug monitoring. Issue 43 (14th May 2015) - Fan, Yiran; Shen, Guanghu; Li, Ping; Xi, Xiaonan; Wu, Haiting; Tian, Hongjun; Lu, Yaxin; Yin, Zheng
<x xml:space="preserve">Abstract</x> An integration of sample pretreatment automation using online SPE technique could provide an easy to use, efficient, sensitive and high quality methods for TDM.